Experimental and mixed analytical–numerical studies for free and forced vibrations of Z-reinforced sandwich plates stiffened by steel ribs. (15th September 2021) - Zhou, Zhiwei; Chen, Meixia; Xiong, Yeping; Jia, Wenchao; Dong, Wenkai; Xie, Kun
Highlights: Free and forced vibrations of the stiffened plate are studied for the first time. A forced vibration test in water is conducted on the manufactured sample. A new method (MA-NM) is proposed for underwater vibration studies of complex plates. The experimental data can be used as benchmark results for future researches. Parametric analyses give some new phenomena and several meaningful conclusions. Abstract: Free and forced vibrations of Z-reinforced sandwich plates stiffened by steel ribs are researched by experimental and mixed analytical–numerical techniques. A test sample of the plate is firstly manufactured and an underwater vibration test is conducted with a random white-noise force. Meanwhile, a mixed analytical–numerical method (MA-NM) is proposed, which uses an analytical homogenization for the Z-reinforced core and coupling finite element and boundary element (FE/BE) analyses for the plate. Natural frequencies given by the MA-NM are compared with ones from the detailed FE model. Forced vibration responses from the MA-NM are validated against the experimental data. Good agreements are obtained and the high accuracy of the MA-NM is demonstrated. Parameters influences are then analyzed through the MA-NM. The core material shows a larger effect on natural frequencies than the reinforcement material. Ribs at the orthotropic midlines greatly enhance the bend stiffness of the whole structure, and ribs at the surrounding sides mainly influence boundary conditions. When in-plane coordinates of the external force near the plate center, vibration responses have fewer resonance peaks and lower amplitudes, while the influence of the thickness direction coordinate could be ignored. The fluid loading reduces both natural frequencies and vibration responses.